Novi realizem v ruski prozi preteklega desetletja in tradicija tridesetih ter štridesetih let 19. stoletja - Podlesnik, Blaž (Primerjalna književnost, 2014)
In Russian prose of the past decade, a group of younger writers, supported by some critics, defined their works as the literature of new realism. This article discusses this literary phenomenon in the broader context of the revival of traditions of realistic fiction in contemporary literature, looking for parallels between the characteristics of the new realism and some forms of nineteenth-century realistic prose.
Keywords: ruska književnost; Russian literature; sodobna ruska proza; realizem; novi realizem; naturalna šola